Inelastic rate coefficients for collisions of N2H+ with H2. Issue 2 (20th May 2020) - Balança, Christian; Scribano, Yohann; Loreau, Jérôme; Lique, François; Feautrier, Nicole
ABSTRACT: N2 H + is one of the first molecular ions observed in the interstellar medium and it is of particular interest to probe the physical conditions of cold molecular clouds. Accurate modelling of the observed lines requires the knowledge of collisional excitation rate coefficients. Thus, we have calculated rate coefficients for the excitation of N2 H + by H2, the most abundant collisional partner. The calculations are based on a new potential energy surface obtained from highly correlated ab initio calculations. This 4D-interaction surface exhibits a very deep well of ≈2530 cm −1 making fully converged scattering calculations very difficult to carry out, when one takes into account the rotational structure of H2 . To overcome this difficulty, two approximate approaches, the adiabatic hindered rotor approach (AHR) and the statistical adiabatic channel model, were tested by comparing the results with those obtained from full 4D close-coupling calculations. The AHR treatment, which reduces the scattering calculations to a 2D problem was found to give the best results at all temperatures and even for transitions involving high N2 H + rotational levels. State-to-state rate coefficients between the 26 first N2 H + rotational levels were calculated for temperatures ranging from 5 K up to 500 K. Using a recoupling technique, rate coefficients are obtained among hyperfine transitions.